Production of reactive persulfide species in chronic obstructive pulmonary disease. Issue 12 (19th July 2017) - Numakura, Tadahisa; Sugiura, Hisatoshi; Akaike, Takaaki; Ida, Tomoaki; Fujii, Shigemoto; Koarai, Akira; Yamada, Mitsuhiro; Onodera, Katsuhiro; Hashimoto, Yuichiro; Tanaka, Rie; Sato, Kei; Shishikura, Yutaka; et al.
Abstract : Background: Oxidative stress is a major aetiological factor driving chronic obstructive pulmonary disease (COPD). Recently recognised as potent antioxidants, reactive persulfide and polysulfide species are biosynthesised by cystathionine β-synthase and cystathionine γ-lyase. The production of reactive persulfide and polysulfide species in the lungs of patients with COPD remain unknown. Objectives: The aim of this study was to examine the production of reactive persulfides and polysulfides, such as glutathione persulfide (GSSH), cysteine persulfide (CysSSH) and glutathione trisulfide (GSSSH), in lung-resident cells and epithelial lining fluid (ELF) obtained from patients with mild to moderate COPD. Methods: Lung tissues, primary lung cells, ELF and sputum were obtained. The amounts of reactive persulfides and polysulfides in the cells and ELF were measured by liquid chromatography–tandem mass spectrometry with β-(4-hydroxyphenyl) ethyl iodoacetamide as a trapping agent for hydroper/polysulfides. The amounts of synthases in the lung tissues, sputum and primary cells were quantified. Results: The amounts of GSSH, CysSSH and GSSSH were decreased in the lung cells and ELF from patients with COPD. The amounts of reactive persulfides and polysulfides in the lung cells had a positive correlation with the degree of airflow limitation. By contrast, the amounts of the synthases were increased in the lung tissues and sputum cells of patients with COPD. Conclusions: We have identified a decrease in reactive persulfide and polysulfide species in the lungs of patients with COPD. These data suggest that the newly detected antioxidants reactive persulfides and polysulfides could be associated with the redox balance in the lungs of patients with COPD.